Knowledge, Attitudes, Age, Education Level Factors to Waste Management - Dwi Noerjoedianto; Oka Lesmana; Qurrota A'yunin (Chakra Brahmanda Lentera Institute, 2022)
Background: waste is one of the environmental problems which can never be solved. Indonesia is one of the countries that have problems with waste. This study aimed to determine the relationship between knowledge, attitudes, age, education level, and waste disposal facilities on waste management. Methods: This study used an analytical survey method with a cross-sectional approach. The population in this study were 398 respondents with a sample of 90 respondents with a sample of 90 respondents with a sampling technique using accidental random sampling. The independent variables in this study were knowledge, attitudes, age, education level, and waste disposal facilities, while the dependent variable was waste management. The measuring tools used are observation sheets and questionnaires. Data analysis was carried out univariate and bivariate (using the chi-square test = 0.05). Results: The results of this study are that there is a relationship between knowledge and waste management (pvalue = 0.015 <0.05), there is a relationship between attitudes and waste management (pvalue =0.023 <0.05), there is no relationship between age and waste management (pvalue =0.928 > 0.05), there is no relationship between education level and waste management (pvalue =0.079 > 0.05), there is a relationship between waste disposal facilities with waste management (pvalue =0.001 > 0.05)` Conclusion: From the results of this study the behavior of traders and waste disposal facilities is very influential on waste management. It is recommended for the manager of the market officer to give direction to the traders to do good waste management, as well as improve the waste disposal facilities in the market.